2022
DOI: 10.1007/s40265-022-01684-5
|View full text |Cite
|
Sign up to set email alerts
|

Molnupiravir: First Approval

Abstract: Molnupiravir (Lagevrio ® ) is an orally-administered antiviral prodrug that inhibits replication of RNA viruses through viral error induction. It is being developed by Merck and Ridgeback Biotherapeutics for the prevention and treatment of Coronavirus disease 2019 (COVID-19). Molnupiravir received its first approval on 4 November 2021 in the UK for the treatment of mild to moderate COVID-19 in adults with a positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 28 publications
0
70
0
3
Order By: Relevance
“… 310 , 311 Molnupiravir has been approved by FDA for clinical use as the first oral drug treating SARS-CoV-2, and it displayed broad efficacy against multiple RNA viruses. 270 , 294 , 312 Studies found that it could effectively inhibit the infection of both SARS-CoV-2 ancestral strain and Omicron variant in vitro (EC 50 3.57–4.15 μM—WT and 1.86–1.95 μM—Omicron). 5 , 263…”
Section: Molecular Characteristics Of Sequence and The Encoded Protei...mentioning
confidence: 99%
“… 310 , 311 Molnupiravir has been approved by FDA for clinical use as the first oral drug treating SARS-CoV-2, and it displayed broad efficacy against multiple RNA viruses. 270 , 294 , 312 Studies found that it could effectively inhibit the infection of both SARS-CoV-2 ancestral strain and Omicron variant in vitro (EC 50 3.57–4.15 μM—WT and 1.86–1.95 μM—Omicron). 5 , 263…”
Section: Molecular Characteristics Of Sequence and The Encoded Protei...mentioning
confidence: 99%
“…Introduction Molnupiravir is a RNA replication inhibitor and an antiviral drug receiving first approval in UK for the treatment of severe acute respiratory syndrome coronavirus (SARS-CoV-2) by 4th of November, 2021. It acts similar to Remdesivir [1,2]. According to Phase 2 and Phase 3 clinical study results, it was generally well tolerated and less adverse events were reported which were found to be not dose related [1,3].…”
mentioning
confidence: 90%
“…Table 2 shows the scientific aspect of the history of infectious diseases [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ], and Table 3 shows infectious diseases studied using molecular techniques, including metagenomics. Different reviews as well as two important books explore this field [ 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: History Of “Plagues”mentioning
confidence: 99%